2006
DOI: 10.1097/00132585-200609000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Devices in Meniscal Repair

Abstract: Preservation of the menisci is increasingly emphasized in orthopedic care of the knee. Techniques are rapidly emerging that allow easier accomplishment of this goal. In particular, the development of all-inside arthroscopic meniscal repair devices has facilitated more ready repair. A number of laboratory and clinical studies have examined these devices and comparisons with more traditional techniques have been made. Numerous reports of potential complications from these new technologies have also been describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…26,43 The 3 arthroscopic techniques used today are the inside-out repair, outside-in repair, and all-inside repair. Although the inside-out repair remains the gold standard of meniscal repairs because of its proven success in a variety of meniscal zones, 14,15,38 the outside-in technique can be useful for anterior tears that are hard to reach through arthroscopic portals, 21 and the all-inside technique has become increasingly popular since the introduction of the Meniscus Arrow (Bionx Implants Inc) in 1993. 3 The all-inside technique has shown reduced operative times, quicker patient recovery, and fewer potential neurovascular complications, especially with tears of the posterior horn.…”
mentioning
confidence: 99%
“…26,43 The 3 arthroscopic techniques used today are the inside-out repair, outside-in repair, and all-inside repair. Although the inside-out repair remains the gold standard of meniscal repairs because of its proven success in a variety of meniscal zones, 14,15,38 the outside-in technique can be useful for anterior tears that are hard to reach through arthroscopic portals, 21 and the all-inside technique has become increasingly popular since the introduction of the Meniscus Arrow (Bionx Implants Inc) in 1993. 3 The all-inside technique has shown reduced operative times, quicker patient recovery, and fewer potential neurovascular complications, especially with tears of the posterior horn.…”
mentioning
confidence: 99%
“…38,44,45,49-51 While the repair technique evolved from earlier all-open meniscal repairs 44,49,50 to less invasive all arthroscopic inside-out and all-inside meniscal repair techniques, 38,45,51 failure rates stayed at a constant level. Investigators previously reported that patient age, 7 time since injury, 28 complex tears, 11 and ligamentous instability 4 are risk factors for poor clinical outcome of meniscus repair; however, little is known about the effect of perioperative NSAID use.…”
mentioning
confidence: 99%
“…Among the three arthroscopic repair methods, the all‐inside repair was the most recently developed, with the expectation of decreasing technical difficulty and operative time 10 . Many devices are currently available 7 , but these are certainly not without shortcomings 13,19–24 . In this age of rapid technological advances, new devices need to be evaluated comprehensively to assure that they are equivalent, if not superior, on biomechanical and clinical grounds to other all‐inside repair devices, as well as to other methods of meniscal repair.…”
Section: Discussionmentioning
confidence: 99%
“…These advantages theoretically lead to fewer neurovascular injuries than occur with the inside‐out and outside‐in techniques. Devices such as staples, arrows, FasT‐fix (Smith & Nephew, Endoscopic Division, Andover, MA, USA) and Rapid‐Loc (DePuy Mitek, Raynham, MA, USA) 7 have emerged with the growing demand for more efficient and effective all‐inside repair devices. Although studies have shown these devices to be efficacious 8–11 , they are not without complications such as aseptic synovitis, chondral injury, cystic hematoma formation, and implant failure 12 .…”
Section: Introductionmentioning
confidence: 99%